THE VILLAGE PEOPLE EMPOWERMENT TO INCREASE SOCIAL WELFARE - Wahyu Edi Purnomo; Desi Wahyuni; Widia Paramita (UBL, 2016)
This paper aims to expose about the empowerment of village community to improve well-being. Community empowerment is an activity that the culprit is a group or community, who do social activities for making changes that the output is in the form of a change towards better or can be called with the agents of development. Empowerment of village community is no stranger anymore, Government programs aimed at empowering communities now no visible or famous arguably average less successful and not populist. The purpose of the existence of community empowerment in particular village community is to improve the standard of living, especially economic development. When the villagers welfare increases then the development education will increase the level of health, When education is already good then it can effect both on the development of human resources and human resources is important in the development of assets in addition to the resources of the Fund as well as infrastructure.The development of various aspects of running smoothly, then they would've success building and it is the starting point for the achievement of well-being. Village community is the most important target object or in terms of the empowerment of the villages, because the starting point of the development of the State is in the village.